2017
DOI: 10.5603/gp.a2017.0027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic value of cervical cytology and HPV HR DNA testing for the diagnosis of low-grade and high-grade squamous intraepithelial lesions across different age groups

Abstract: Objectives: To assess the diagnostic value of cervical cytology and HPV HR DNA testing for the diagnosis of low grade and high-grade squamous intraepithelial lesions across different age groups. Material and methods:The study included 1103 patients, age 25-70 years. All patients underwent in-depth diagnostic tests following either an abnormal Pap test result or a clinically suspicious cervical lesion. In all women the following examinations were performed: a molecular test detecting 14 high-risk types of HPV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The level of agreement did not differ much by age group, and this is in accordance with a recent systematic review done by Yeh et al 19 However, the sensitivity varied by age with self-sampling having a higher sensitivity in women younger than 40 years of age (72.3%) than among women older than 40 years of age (51.4%) but with the highest specificity among the older women (99.0%). Along the same lines, Paluszkiewicz et al 20 reported a higher sensitivity of the HPV test for detecting high-grade squamous intraepithelial lesions for women below younger than 50 years of age, whereas Labani and Asthana 21 found that the performance of self-sampling did not vary by age. Our finding that some HPV infections were missed by the self-collection method, especially in older women, yielding a lower sensitivity could be of concern as cervical cancer in this age group is high.…”
Section: Discussionmentioning
confidence: 92%
“…The level of agreement did not differ much by age group, and this is in accordance with a recent systematic review done by Yeh et al 19 However, the sensitivity varied by age with self-sampling having a higher sensitivity in women younger than 40 years of age (72.3%) than among women older than 40 years of age (51.4%) but with the highest specificity among the older women (99.0%). Along the same lines, Paluszkiewicz et al 20 reported a higher sensitivity of the HPV test for detecting high-grade squamous intraepithelial lesions for women below younger than 50 years of age, whereas Labani and Asthana 21 found that the performance of self-sampling did not vary by age. Our finding that some HPV infections were missed by the self-collection method, especially in older women, yielding a lower sensitivity could be of concern as cervical cancer in this age group is high.…”
Section: Discussionmentioning
confidence: 92%
“…HPV infects the epithelial surface and can lead to the development of proliferative benign lesions in the skin, mucosa and genital tract ( 3 ). Genital HPV infection is among the sexually transmitted infections (STIs) with the highest incidence and prevalence worldwide ( 4 – 7 ) and is associated with the development of low- to high-grade squamous intraepithelial lesions (LSIL and HSIL, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…HPV infection is more common in young women. In some studies, the highest proportion of HPV positivity is reported in women aged 31-40 or 35-45 and in those younger than 20 years 24 , 25 , 31 , 32 . However, in studies performed in Turkey, it is reported that women between the 30 and 39 yr have the highest HPV positivity 6 , 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%